Polarization modulation profiles in ferroelectric superlattices - Chew, Khian Hooi; Shin, F.G.; Iwata, M. (2009)
A Landau-Ginzburg continuum model for describing a periodic superlattice consisting of alternating ferroelectric and paraelectric layers is presented. An interface coupling term is introduced to describe the interaction at the interface between the two constituent layers. Explicit expressions to describe the order parameter profiles were derived and illustrated. Our study reveals that the interface-induced polarizations in the paraelectric layer plays an important role to determine the polarization modulation profile of a ferroelectric superlattice.